2014
DOI: 10.1080/08959420.2014.854648
|View full text |Cite
|
Sign up to set email alerts
|

Making the Right Moves: Promoting Smart Growth and Active Aging in Communities

Abstract: This article describes an award program sponsored by the U.S. Environmental Protection Agency for excellence in smart growth and active aging. Having examined qualitative and quantitative data, we suggest that any community can foster changes to improve the health and well-being of its aging population. Diverse winners took unique paths to change their built environments and encourage physical activity. The policy changes undertaken by the award winners have both short- and long-term benefits that are importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Rural communities’ ability to become age-friendly was influenced by contextual factors such as size, location, demographic composition, ability to secure investments, and leadership [50]. Communities mostly assess their success by considering the level of community involvement, surveys, program attendance and number of classes taught, as well as incorporating the needs of older adults in organisations’ and agencies’ strategic planning [53]. Moreover, research has shown differences in rural versus urban communities’ trajectory and timeline for improving age-friendliness.…”
Section: Introductionmentioning
confidence: 99%
“…Rural communities’ ability to become age-friendly was influenced by contextual factors such as size, location, demographic composition, ability to secure investments, and leadership [50]. Communities mostly assess their success by considering the level of community involvement, surveys, program attendance and number of classes taught, as well as incorporating the needs of older adults in organisations’ and agencies’ strategic planning [53]. Moreover, research has shown differences in rural versus urban communities’ trajectory and timeline for improving age-friendliness.…”
Section: Introductionmentioning
confidence: 99%
“…Several land-use planning and community design alternatives such as Smart Growth and livable communities have emerged in recent years. Such movements call for a more integrated design of neighborhoods, with less fragmentation between residential and work places, thus facilitating active transportation, while making it safe and enjoyable ( Degaspari, 2013 , Fenton, 2005 , Jerrett et al, 2013 , Sykes and Robinson, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Successful ageing refers to multidimensional involvement that is inclusive of physical, functional, psychological, and social health (Phelan, Anderson, LaCroix, & Larson, 2004). In determining active ageing, the elderly should be physically active and indulge in biking, walking, and fitness trails, to name a few, so as to gain strength, maintain flexibility, and increase endurance (An, S., Lee, Y. and Kim, 2013;Dahany et al, 2014;Sykes &Robinson, 2014). Paúl, Ribeiro, andTeixeira (2012) revealed that the economic determinants, physical environment, health, and social services are relevant to active ageing, which are also closely linked with personal needs, resources, and outcomes.…”
Section: Active Ageing and Muslim Overviewmentioning
confidence: 99%